Primary and Secondary Genotoxicity of Nanoparticles: Establishing a Co-Culture Protocol for Assessing Micronucleus Using Flow Cytometry - Vallabani, N. V. Srikanth; Karlsson, Hanna L. (Frontiers in Toxicology, 2022)
Genotoxicity is an important endpoint to assess for understanding the risks associated with nanoparticles (NPs). Most genotoxicity studies performed on NPs have focused on primary genotoxicity analyzed by comet- or micronuclei (MN) assay using microscopic scoring. Here, we established a protocol for a more efficient version of MN assessment using flow cytometry and, importantly, both primary and secondary (inflammation-driven) genotoxicity was assessed. Human bronchial epithelial cells (HBEC-3kt) were exposed to nickel oxide (NiO) NPs directly or indirectly. The indirect exposure was done to assess secondary genotoxicity, and in this case immune cells (THP-1 derived macrophages) were exposed on inserts and the HBEC were cultured in the lower compartment. The results in monocultures showed that no increased MN formation was observed in the HBEC cells but instead a clear MN induction was noted in THP-1 cells indicating higher sensitivity. No MN formation was either observed when the HBEC were indirectly exposed, but an increase in DNA strand breaks was detected using the comet assay. Taken together, the present study emphasizes the feasibility of assessing primary and secondary genotoxicity and, furthermore, shows a clear MN induction in THP-1 monoculture following NiO NPs exposure.